2009
DOI: 10.1159/000218115
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Dependent Induction of Cathelicidin-Related Antimicrobial Peptide in Murine Mast Cells by Lipopolysaccharide

Abstract: Background: An important aspect of the innate immune response to pathogens is the production of anti-microbial peptides such as cathelicidin-related antimicrobial peptide (CRAMP), the murine homologue of human cathelicidin LL-37. In this study, mechanisms regulating LPS-induction of CRAMP gene expression in mast cells were investigated. NF-κB and MAPK pathways were the focus of investigation. Methods: Mouse bone marrow-derived mast cells were grown in culture and stimulated with LPS. MAPKs and NF-κB were monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 101 publications
4
51
0
Order By: Relevance
“…Therefore, the observed activation of the MyD88 -IRAK-4 signaling pathway and NF-B could be attributed to the absence of ESAT-6 in M. bovis BCG. Moreover, activated NF-B was also shown to activate Camp expression (62). In agreement with those results, we also observed decreased Camp expression levels after the inhibition of nuclear translocation of NF-B in M. bovis BCG-infected cells.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the observed activation of the MyD88 -IRAK-4 signaling pathway and NF-B could be attributed to the absence of ESAT-6 in M. bovis BCG. Moreover, activated NF-B was also shown to activate Camp expression (62). In agreement with those results, we also observed decreased Camp expression levels after the inhibition of nuclear translocation of NF-B in M. bovis BCG-infected cells.…”
Section: Discussionsupporting
confidence: 91%
“…A resent study also shows the requirement of NF-B for lipopolysaccharide (LPS)-induced stimulation of CRAMP in murine mast cells (47). Although we demonstrated that ER stress increases CRAMP expression in murine epidermis ex vivo, it remains to be resolved whether the C/EBP␣ signal is also required for the regulation of CRAMP under non-stressed conditions.…”
Section: Discussionmentioning
confidence: 69%
“…However, overexpression of MEKK2 did not affect LPS-induced cathelicidin-related antimicrobial peptide gene expression in mast cells 9 . In our experiments, MEKK2 knockdown only slightly inhibited LPS-induced ERK1/2 activation, suggesting that endogenous MEKK2 might be dispensable or redundant for ERK1/2 activation in TLR4 signalling.…”
Section: Discussionmentioning
confidence: 86%
“…It was reported that MEKK2 was associated with TRAF6 and phosphorylated following LPS stimulation in RAW264.7 cells, and overexpression of MEKK2(S519A) mutant inhibited LPS-induced Elk1 luciferase reporter gene expression in the cells, suggesting that MEKK2 might be involved in TLR4 signal transduction 8 . However, overexpression of MEKK2 did not affect LPS-induced cathelicidin-related antimicrobial peptide gene expression in mast cells 9 . The exact role of endogenous MEKK2 in TLR-mediated immune responses requires further investigation.…”
mentioning
confidence: 86%